Mental health risk factors during the first wave of the COVID-19 pandemic. Issue 6 (27th November 2021) - Prata Ribeiro, Henrique; Ponte, André; Raimundo, Miguel; Reis Marques, Tiago
Abstract : Background: During the first wave of the COVID-19 pandemic, distancing measures were enforced to reduce virus spread, which likely had an impact on the overall mental health of the population. Aims: To investigate the prevalence of mental health outcomes (depression, anxiety and insomnia), and associated risk factors, during a physical distancing period imposed in the first wave of COVID-19. Method: During the first month of Portugal's state of emergency, an online survey was created and disseminated through social media channels. Sociodemographic and clinical variables were assessed via self-reported questionnaires. Univariate linear regressions were used to identify associations between the collected variables and mental health outcomes. Multivariate regression analyses were performed to identify independent risk factors for clinical outcomes, with adjustment for potential confounders. Results: We analysed data from 1626 participants: a significant proportion showed depression (30.2%), anxiety (53.1%) and insomnia (36.3%) symptoms. Multivariate regression models showed that being male and working from home were protective for all mental health outcomes analysed, whereas the perception of infection, being under psychiatric care and taking medication were risk factors ( P < 0.05). Days in isolation and being unemployed were risk factors for depression and insomnia ( P < 0.05). Younger age and being a student were risk factors for depression, whereas being a healthcare professional was protective ( P < 0.05). Indirect contact with COVID-19 was a risk factor for anxiety ( P < 0.05). Conclusions: COVID-19-related distancing measures were associated with high levels of adverse mental health symptoms. Several risk factors were associated with these symptoms, which highlight the importance of identifying vulnerable groups during physical distancing periods.